The hitman's bodyguard [videorecording (Blu-Ray)] - O'Connor, Tom (Screenwriter); Reynolds, Ryan; Jackson, Samuel L.; Oldman, Gary; Hayek, Salma, 1966-; Atli Örvarsson; O'Loughlin, Jules (Summit Entertainment, 2017)
The world's top protection agent is called upon to guard the life of his mortal enemy, one of the world's most notorious hitmen.